Effect of Different Roughage Sources in Fermented Total Mixed Ration and Energy Intake on Meat Quality, Collagen Solubility, Troponin T Degradation, and Fatty Acids of Native Thai Cattle Longissimus Muscle - Achara Lukkananukool; Sineenart Polyorach; Kritapon Sommart; Chanporn Chaosap (My University, 2023)
The effects of roughage sources in the fermented total mixed ration (FTMR) and the level of energy intake on meat quality, collagen solubility, and troponin T degradation in longissimus thoracis (LT) muscle of native Thai cattle (NTC) were investigated. Results showed that roughage source affected fatty acid composition in the LT muscle (p < 0.05), as NTC fed Pakchong 1-Napier-based FTMR had higher monounsaturated fatty acid content and ω 6:ω 3 ratio. The high-energy ad libitum group had lower drip loss, lower shear force, and higher percent collagen solubility (p < 0.05). However, energy intake had no effect on troponin T degradation and fatty acid composition (p > 0.05). Longer aging of 14 days showed lower shear force values, higher collagen solubility, and troponin T degradation rate but higher cooking loss (p < 0.01). In conclusion, the meat quality of NTC could be improved by ad libitum feeding with NG-FTMR, as their meat had higher MUFA content, lower drip loss, lower shear force, and higher collagen solubility. In addition, the tenderness of NTC meat could be further improved by longer aging of 14 days post-mortem.
Keywords: Longissimus Thoracis; Meat and Animal Product Quality